Korolu the singing bandit - Walker, Barbara K; Nodjoumi, Nickzad (New York : Thomas Y. Crowell Company, 1970)
The story of Korolu, the Turkish folk hero, who became an outlaw to avenge his father, blinded by a great landowner.